Symbol Aesthetics in Mesopotamia Pottery - Abdui Hafedh, Omar Mohmmad Samer; Jafari, Hamideh (Journal of Humanities & Social Sciences, 2023)
The art of pottery is part of the history of human arts and has had a great influence on different cultures throughout the ages، It includes many techniques and methods that are used to shape clay and give it beauty and function، Therefore، this research was to explore the aesthetics of the symbol in the pottery of Mesopotamia. Where his study was divided into four main chapters، namely the first chapter، and the research problem was addressed through a main question، which is: "What are the aesthetics of the symbol in the pottery of Mesopotamia?" The importance of the current research lies in the study of the subject of the aesthetics of the symbol in the pottery of Mesopotamia and what this subject carries of artistic values، while observing the cultural impact of the country، Whereas، the need for it lies in the fact that it benefits students of faculties of fine arts and their institutes and all specialists in the art of ceramics and pottery. In the second chapter، the theoretical framework for the research was presented. Where the focus was on the concept of beauty and a review of the aesthetic and philosophical foundations and how they interact with the plastic arts. The concept of aesthetic symbolism and its role in the plastic arts was also reviewed. The philosophical arguments that deal with the symbol and its use in the plastic arts were reviewed، The chapter concluded by highlighting the most important indicators that resulted from the theoretical framework presented، and in the third chapter، the research community was identified، which includes pottery dating back to the Mesopotamian civilization، The specimen was identified from pottery sculptures. The descriptive research methodology was used to analyze these samples from Mesopotamia pottery، and finally in the fourth chapter، The samples were analyzed and the results were presented، the most important of which is that the symbol conveys through its representation in the pottery of the ancient era the traditions، landmarks and situation of the ancient era and what the sculptural and pottery arts were like، The symbol always refers to an inner meaning that emanates from within the pottery products themselves، and may or may not convey the idea to the viewer.
Keywords: aesthetics; symbol; pottery; Mesopotamia; symbol aesthetics; Mesopotamia pottery